UNIVERSAL VOLTAGE-MODE BIQUADRATIC FILTER SYNTHESIS USING NODAL ADMITTANCE MATRIX EXPANSION - Trần, Hữu Duy (Trường Đại học Đà Lạt, 2023)
This paper presents a systematic synthesis procedure for generating universal voltage-mode biquadratic filters based on the nodal admittance matrix expansion. The obtained eight equivalent circuits can realize all five standard filter functions namely lowpass, bandpass, highpass, notch and allpass employing only two active elements. The obtained circuits offer the following advantages: five inputs and two outputs, simple circuit configuration, orthogonal controllability between pole frequency and quality factor, and low active and passive sensitivities. The workability of some synthesized filters is verified by HSPICE simulations to demonstrate the usefulness of the proposed method.